Evaluating the antecedents of entrepreneurs' Al-Falah (success) in Kedah - Siti Nadirah, Mohammad Nawawi (2019)
Entrepreneurship has undeniable contribution to individuals, society and to the economic growth of the country and entrepreneurship from Islamic perspective is to achieve al-falah which is to seek the pleasure of Allah and not profit oriented. The numbers of company termination is increasing as recorded in the SSM 2017 annual report. In order to avoid failure, positive action must be conducted to ensure the successfulness of the entrepreneurs. This study then attempted to examine the relationship between five antecedents and the entrepreneurs’ al-falah (success) in Kedah and the respondents is the entrepreneurs at Pekan Rabu Alor Setar and Kompleks Haji Ismail Group (HIG) Langkawi. Quantitative research design is employed in this study where survey is used as the main instrument for gathering data. The antecedents examined are honesty, tenacity, managing risk, religiosity and Islamic motivation, towards the dependent variable which is the al-falah (success) of the entrepreneurs. The sample study comprises 196 entrepreneurs and the data is analysed using SPSS version 21 and Smart Partial Least Squares (PLS) method version 3. The finding of the study revealed that three antecedents have positive relationship towards the entrepreneurs’ al-falah (success); managing risk, religiosity and Islamic motivation while the most influential antecedent for the entrepreneurs to achieve al-falah is the managing risk. This study then can improve the performance of the entrepreneurs and the related body or institution can develop and conduct relevant program to the entrepreneurs. This action consequently will contribute to the economic growth. Further study can be conducted within selected industry or business type at larger sample.